Motivational Impact Factors in the performance of colaborators and lecturers - Mindelo case study (Revista Lusófona de Economia e Gestão das Organizações, 2017)
Motivation at work has been a research topic increasingly relevant due to its importance in the organizational culture. Research shows that low levels of motivation reflect various forms of costs for the organization. On the other hand, high levels of motivation translate into job satisfaction, productivity and improved quality of products and services.Taking into account the influence of internal and external factors in motivation at work, this study aims to understand the impact of motivational factors of employees and teachers in the success of the University of Mindelo (Uni-Mindelo) in Cape Verde.For this exploratory type case study, a questionnaire survey was fulfilled in which 81 employees and teachers attended. For the analysis of the results the two types of motivation and compared were quantified.The results show that the motivational factors of the respondents are similar and are mostly at  satisfactory levels, which reinforces the idea that not all performance issues that occur in organizations are caused by low motivation. In this case, the success of the University can pass through the creation of their own teaching staff, by creating partnerships with organizations and with the construction of infrastructure that make nice academic activity.